Erkenntnisse zum Lebenszyklus von Byctiscus betulae (Linné, 1758) aus den Weinbauanlagen von Odobesti, Kreis Vrancea / Rumänien (Coleoptera: Curculionoidea, Rhynchitidae). - Antonie, Iuliana; Teodorescu, Irina; Oprean, Letiţia (Contributions to Entomology = Beiträge zur Entomologie, 2006)
This study was conducted in Odobeti (Vrancea) Vineyard Region. In this vine-growing ecosystem a mass outbreak of Byctiscus betulae L. which lasted for 4 years (2000-2003) was studied at regular intervals of 3-4 weeks. - Oviposition was investigated on 12 varieties of vine, by counting the leaf-rolls of all stages and the number of adults on six stems of each variety of vine. Total material comprised 728 leaf-rolls and 452 adult specimens. Research on the egg and larval stages was undertaken in 2000. From 766 leaf-rolls were extracted 534 healthy eggs; 392 parasite eggs; 179 neonate larvae; 1274 L1 larvae; 898 L2 larvae and 6 L3 larvae. The low percentage of L3 larvae led us to believe that the development of the last larval instar takes place in the ground. Experimental evidence for this was later obtained. - In 2000-2001 we made 65 searches in the soil between previously sampled stems of vines of the Aligote variety on arba Hill. No pupae of B. betulae could be found. In 2002 pupae could only be obtained in the laboratory. The first adult was reared under humidity controlled conditions a week after the first pupa was formed. The pupa is stenohygrous, formed only at approximately 50-55% relative humidity.